Morphology and surficial sediments of the Waldemar River confined outwash fan (Kaffiøyra, Svalbard) - Weckwerth, Piotr; Greń, Katarzyna; Sobota, Ireneusz (Bulletin of Geography. Physical Geography Series, 2017)
The development and evolution of confined outwash fans in high Arctic regions depend on the rate of meltwater discharge which is directly related to the glacier ablation rate associated with climate conditions. Another factor controlling outwash fan morphology (e.g. distributive channels depth and width) are processes of fluvial erosion, transport and sediments deposition. All these factors have not previously been considered in relation to the evolution of confined outwash fans incised into the top of permafrost which commonly occur in the forefield of a subpolar glacier and mountains in the high Arctic regions. Morphology and surficial sediments of a confined outwash fan of the Waldemar River (NW Spitsbergen, Svalbard) were analysed on the basis of geomorphological and sedimentological researches. Results of our investigations show multiple relations between the depth and width of distributary channels, fan slope and textural features of glaciofluvial surficial sediments supplied into the fluvial system from glacier and as a result of lateral fluvial erosion of permafrost.